Unlocking the Potential of Green Gravel Production for Efficient Kelp Restoration: How Seeding Density Affects the Development of the Golden Kelp Laminaria ochroleuca - Silvia Chemello; Inês Amorim Dos Santos; Isabel Sousa-Pinto; Tânia Ribeiro Pereira (Phycology)
Kelp forests are facing a global decline due to climate change and human-induced stressors, underlining the urgency for proactive interventions. Among the most used restoration methods, “green gravel” has emerged as a promising solution for the recovery of degraded kelp forests. While initial findings suggest its potential effectiveness, green gravel remains a novel approach that requires fine-tuned protocols and optimisation across all stages of the process. In this study, we assessed the performance of two different seeding densities for kelp growth on green gravel to optimise the use of seeding material. Our results show that, while the juveniles in the high-density treatment grew faster, they also had a higher mortality rate during green gravel production. This was a hypothesised outcome, as growing sporophytes reared under laboratory conditions allows for faster production of a large number of individuals, increasing competition for space, which may drive higher mortality rates. Comprehensive experimentation is essential to unlock the full potential of green gravel and ensure its efficiency in all process steps, to achieve successful kelp forest restoration. Well-defined and optimised protocols are indispensable for minimising production costs, simplifying logistics, and allowing future efforts to scale up.